Alguns aspectos da proposta de reforma curricular de Euclides Roxo - Rabello, Paula Corradi (2014)
This paper discusses some aspects of the reform movement in mathematics education in Brazil during the first half of the twentieth century. We selected as document for analysis the work A Matemática na Educação Secundária, from Euclides de Medeiros Guimarães Roxo, published in 1937. In the work, the author, responsible for the main guidelines for the reform of mathematics education at the time, justifies his proposals supported by the international discussion started in 1908, with the "V International Congress of Mathematics". The analysis of the document points to an ideological conflict between the international reform proposed by Felix Klein, who Roxo has as his main source of reference, and the brazilian movement of curriculum reform. Our study provides evidence that point to the differences between the two proposals. The progressive school in place in Brazil from 1920 until 1940, seeking an education focused on the transformation of society, differs from the german proposal in their curriculum reform that has as primary goal bringing the teaching of mathematics closer to the industrial and scientific development of Germany during the beginning the twentieth century. This aspect is evidenced in our study of the work of Felix Klein, entitled Elementary Mathematics from an Advanced Standpoint, published in 1945. With this work it was possible to conclud that the influence of Felix Klein became more restricted to speech than to the perception of Roxo on the reform. This would could have happened because, while North America and Brazil had the theoretical foundation based on New School, focusing on the student and on an education capable of reforming society, Germany, with a more stable social situation, sought to leverage industry stimulating the sciences, which would prevent a reproduction of the German reform model in Brazil